The impact of funeral costs on households in the Thulamela Municipality of Limpopo Province - Matodzi, T. H. (My University, 2007)
The main purpose of this study was to investigate the impact of the funeral costs on households. This study was of greater importance in that it makes the public to be aware of ever increasing costs and how this is fundamentally damaging the economic situation of the poor people in the Thulamela Municipality. The major findings of the study were that there existed a gap between what was socially expected at a funeral and what the households could afford in arranging for the funerals. The households used maximal amounts of what they got from burial societies and block contributions. The funerals were not only attended by relatives and friends assisted by undertakers as this would minimize the amounts used, but were attended by multitudes of people who, at the end of the funeral, expected to be entertained with food and drinks. An interesting feature that emerged related to gender was that, in the area of study, women had more to say pertaining to issues of funeral arrangements. In most cases, they were the ones who joined burial societies and gave each other practical support at the time of death. This study is qualitative in nature. The qualitative approach helped the researcher to gain in-depth knowledge about the impact of death in the specific area of study. To explore the topic fully, the researcher conducted focus group discussions and interviews. The respondents in the focus discussions were selected from the households that had bereavement within the last five years directors of five funeral parlours in the municipality were also interviewed. The study highlighted the influence of funeral directors on the expenditure of households in the Thulamela Municipality. The study outlines the misappropriation of funds accumulated over a long period of time in a one day funeral service. The study further revealed the role played by formal insurers, funeral parlour, burial societies and funeral schemes that deceive households in the Thulamela Municipality part of their little income.
Thesis (M.Dev.) --University of Limpopo, 2007.
Keywords: Funeral rites and ceremonies; Burial; Funeral costs